Mediation dispute resolution procedure: theoretical and practical aspects - Череватюк, Вікторія Богданівна; Сірук, Катерина Леонідівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
A definition of mediation is grounded in the article, the features of mediation dispute resolution procedure is analyzed. Attention is also paid to the preparation and participation of mediator in the negotiation process. Moreover, the authors review problems of legislative provision of mediation in Ukraine and outline their solutions. It’s concluded in the article that mediation is an alternative way of dispute resolution that appears to be a structured negotiation process that is held by independent, neutral and qualified mediator who helps the parties of a dispute to reach an agreement on their own and voluntarily that would meet the interests of both sides. Mediation doesn’t focus on searching and proving the rightness of one or other party. Its aim is to activate the potential of argument’s parties making them look for mutually beneficial solution of the dispute that would prevent business relationships. Mediator is responsible for the negotiation process’ organization that helps in searching of the best mutual decision. With the purpose of better understanding of mediation procedure and according to the all mentioned above the authors suggest to define it as a process of preparing and holding the main stages of mediation.